Self-realization through Confucian learning : a contemporary reconstruction of Xunzi's ethics - Tang, Siu-Fu, 1974- (Albany : State University of New York Press, 2016)
"Self-realization through Confucian Learning reconstructs Confucian thinker Xunzi's moral philosophy in response to the modern focus on self-realization. Xunzi (born around 310 BCE) claims that human xing ("nature" or "native conditions") is without an ethical framework and has a tendency to dominate, leading to bad judgments and bad behavior. Confucian ritual propriety (li) is needed to transform these human native conditions. Through li, people become self-directing: in control of feelings and desires and in command of their own lives."--Page 4 of cover.
Desires and their form of expressionChapter 4. Ritual Propriety and the Good Life; The self and the good; The petty man and the noble man; Understanding the Way; Community and the self; Ritual propriety as self-interpretation; Conclusion; Notes; Bibliography; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Xunzi, -- 340 B.C.-245 B.C.; Confucian ethics; Philosophy, Chinese -- To 221 B.C.; Philosophy, Confucian -- China; PHILOSOPHY -- Eastern; Xunzi, -- 340 B.C.-245 B.C.; Confucian ethics; Philosophy, Chinese; Philosophy, Confucian; China; To 221 B.C.; Electronic books